2013
DOI: 10.4236/health.2013.58a3008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a school based childhood obesity intervention for posture and comfort

Abstract: Background: Research shows that students who are more active throughout the day have fewer reports of body part discomfort and greater energy expenditure needed to combat childhood obesity. Many factors may contribute to the overall health of the child, including the postures that are required to complete assigned tasks at their school workstations. Decreasing sedentary behaviors in children through the use of standing desks at school has been shown to increase calorie expenditure and may be a viable approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…Thus, a final sample of 8 articles was identified for the present review. Two publications that reported findings pertaining to the same intervention 22,23 were consolidated in the results of the primary study publication. 24 Table 1 summarizes the characteristics of the studies included in our review.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Thus, a final sample of 8 articles was identified for the present review. Two publications that reported findings pertaining to the same intervention 22,23 were consolidated in the results of the primary study publication. 24 Table 1 summarizes the characteristics of the studies included in our review.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Mark Benden (2011Benden ( -2013 and his team at Texas A&M have also collected anthropometric data on more than 500 children in relation to school furniture that they hope to publish in the next 2 years. Most recently the team released ergonomics details on posture and comfort for children in school furniture with design implications for obese children (Benden, Pickens, Shipp, Perry, & Schneider, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Research for the type of information needed in this standard came from sources such as the CAESAR anthropometric database (Harrison & Robinette, 2002) (2003); regional anthropometric data from Benden (2011Benden ( -2013; CHILDATA (June 1995; Norris & Wilson, 1995); sizing of current educational seating on the market; and peer-reviewed papers on use and proprietary industry experience based on internal testing and warranty experience. When using the NHANES (2005NHANES ( -2008 data sets, all persons older than 22 years were deleted from the subject pool, as were all pregnant girls.…”
Section: The Hf/e Connectionmentioning
confidence: 99%
“…However, standing for prolonged periods of time during the school-day is not common practice in the United States, leading to questions regarding whether prolonged standing leads to changes in the levels and anatomical locations of discomfort not typically associated with prolonged periods of sitting. As part of a larger intervention, Benden et al (2013) aimed to examine student's sitting and standing posture along with self-reported discomfort while using stand-biased or traditional seated desks. Researchers further sought to understand whether there were any unidentified consequences to implementing stand-biased desks in the classroom which may actually support the retention of traditional seated desks.…”
Section: Posturementioning
confidence: 99%
“…Stand-biased desks are considered a mild environmental stimulus because accessibility alone may not have a sufficient impact on activity behaviors without additional stimuli such as teacher encouragement, or the conscious decision to stand or otherwise change a behavior. The use of a stand-biased desk has been found to result in less postural discomfort overall, however no significant differences have been found indicating less time is spent in nonpreferred postures during use, compared to students seated at traditional desks (Benden et al, 2013). As a result of stand-biased desk use, several studies measuring postural behaviors have also reported significant decreases in sitting time during the school day, with both standing and stepping times increasing as a result (Aminian et al, 2015;Clemes et al, 2015;Contardo et al, 2016).…”
mentioning
confidence: 99%